2014
DOI: 10.1039/c4cp00087k
|View full text |Cite
|
Sign up to set email alerts
|

In situ X-ray powder diffraction studies of hydrogen storage and release in the Li–N–H system

Abstract: We report the experimental investigation of hydrogen storage and release in the lithium amide-lithium hydride composite (Li-N-H) system. Investigation of hydrogenation and dehydrogenation reactions of the system through in situ synchrotron X-ray powder diffraction experiments allowed for the observation of the formation and evolution of non-stoichiometric intermediate species of the form Li1+xNH2-x. This result is consistent with the proposed Frenkel-defect mechanism for these reactions. We observed capacity l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 37 publications
9
43
0
Order By: Relevance
“…Key to the widespread deployment of hydrogen, particularly for mobile applications, is high‐density reversible storage. Complex metal hydrides possess both large gravimetric and volumetric hydrogen densities, up to 15 wt% and over 100 kg m −3 1a,2. The two major challenges preventing the widespread use of complex metal hydrides are the sluggish kinetics at low temperatures and the formation of stable intermediate phases that reduce the capacity over time and shift thermodynamic phase equilibria unfavorably.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Key to the widespread deployment of hydrogen, particularly for mobile applications, is high‐density reversible storage. Complex metal hydrides possess both large gravimetric and volumetric hydrogen densities, up to 15 wt% and over 100 kg m −3 1a,2. The two major challenges preventing the widespread use of complex metal hydrides are the sluggish kinetics at low temperatures and the formation of stable intermediate phases that reduce the capacity over time and shift thermodynamic phase equilibria unfavorably.…”
mentioning
confidence: 99%
“…In addition, knowledge of phase conversions is an essential aspect of a comprehensive understanding of hydrogenation and dehydrogenation because it provides evidence that can help determine which process limits the rate of the phase transformation. The formation of Li 2 NH from LiNH 2 involves the diffusion or migration of highly mobile Li + from LiH to LiNH 2 to counter the transport of hydrogen from one NH 2 − to another and eventually to the hydride in LiH 2,8b,10. The phases have been proposed to form in a roughly core–shell arrangement, with the imide forming on the exterior of a LiNH 2 ‐rich core which shrinks during dehydrogenation as the imide propagates inward.…”
mentioning
confidence: 99%
“…The PCI displays a slope down toward the complete dehydrogenation. This behavior in the PCI curve of the LiNH 2 eLiH system can be interpreted on the basis of recent investigations [30,31]. These studies have demonstrated that the LiNH 2 and Li 2 NH are the dominant phases in the hydrogenated and dehydrogenated states respectively, and different phases with intermediate stoichiometry exist between both compounds.…”
Section: Resultsmentioning
confidence: 86%
“…In this context, David et al [30] proposed a Frenkel defect model based on the migration of Li þ and H þ ions for dehydrogenation (and hydrogenation). The recent work of Makepeace et al [31] demonstrates the formation and evolution of non-stoichiometric intermediate species of the form Li 1þx NH 2Àx . Then, the sloping behavior of the PCI curve can be related with the conversion of LiNH 2 into Li 2 NH, involving the formation of non-stoichiometric species.…”
Section: Resultsmentioning
confidence: 98%
“…David and coauthors, noted that the non-stoichiometric intermediates reported as Li 1+x NH 2−x species are formed during desorption and absorption of the Li-N-H system, in accordance with the Frenkel defect model [24].…”
Section: Li-n-h Systemmentioning
confidence: 92%